1985
DOI: 10.1128/iai.47.2.575-578.1985
|View full text |Cite
|
Sign up to set email alerts
|

Highly toxinogenic but avirulent Park-Williams 8 strain of Corynebacterium diphtheriae does not produce siderophore

Abstract: The highly toxinogenic Park-Williams 8 strain of Corynebacterium diphtheriae grows slowly in vitro and is avirulent. C. diphtheriae Park-Williams 8 is defective in iron uptake and does not produce the corynebacterial siderophore corynebactin. Addition of partially purified corynebactin' stimulated iron uptake and growth of iron-deprived C. diphtheriae Park-Williams 8 cells. Corynebacterium diphtheriae Park-Williams 8 (PW8), isolated in 1896 by Park and Williams (13), is used as the source of toxin for the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These mutants are, in general, also affected in terms of iron regulation of toxin production. One of the mutants, defective in the production of the corynebacterial siderophore, is best known as strain PW8, which is a very highly toxinogenic strain of C. diphtheriae (86,87). Furthermore, recent evidence suggested that the cloned diphtheria toxin promoter is iron regulated in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…These mutants are, in general, also affected in terms of iron regulation of toxin production. One of the mutants, defective in the production of the corynebacterial siderophore, is best known as strain PW8, which is a very highly toxinogenic strain of C. diphtheriae (86,87). Furthermore, recent evidence suggested that the cloned diphtheria toxin promoter is iron regulated in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of DT by C. diphtheriae is inhibited by iron, and transcription of the tox operon in C. diphtheriae decreases under high-iron conditions (23, 26; Tai and Holmes, manuscript in preparation). Furthermore, the iron-uptake system of C. diphtheriae is induced during growth in lowiron conditions (40), several mutants defective in iron regulation of toxin synthesis have altered iron-uptake systems (12), and the highly toxinogenic PW8 strain of C. diphtheriae is defective in producing corynebacterial siderophore (41). A decade ago Murphy and Bacha postulated that the tox operon of C. diphtheriae is negatively regulated by a protein repressor that uses iron as a corepressor and suggested that the repressor is encoded by the bacterial chromosome (33).…”
Section: Discussionmentioning
confidence: 99%
“…The corynebactin transport (ciuA-D) gene cluster was present in all genomes, with one exception, whereas the corynebactin synthesis (ciuEFG) locus was absent or incomplete in only 5.4% of genomes (n=29 Mitis, n=25 Gravis); of these, 33 lacked the ciuE gene, which is essential for siderophore synthesis. One of the genomes lacking ciuE corresponds to the vaccine strain PW8, which is defective for corynebactin synthesis (Russell & Holmes, 1985). The heme-acquisition genes hmuTUV were also largely conserved (921 genomes; 94.4%).…”
Section: Lineages Gravis and Mitis Differ In The Presence Of Pathogen...mentioning
confidence: 99%